Collaborative teaching-learning between college and industry: A case study of steel practice subj ect matter in the technical faculty ofYogyakarta State University - Suparman Suparman (JOURNAL OF EDUCATION, 2008)
Abstract: In vocational secondary school, a collaborative teaching-learning model is known as a dual education system where the students practice  in industries. Generally, that system is successful although there are variations among the school. Such collaboration needs relatively high cost and complicated coordination. As an alternative, teaching-learning collaboration between college and industry can be conducted by inviting guest lecturers from the well industry. Thepresent study is aimed at obtaining a model where practice products are marketable and students have co-operative attitudes in team work. Three teaching-learning models are compared. First, the teaching-learning process of thefirst half semester is conducted by a lecturer in college while the rest is conducted by two lecturers in industry. Second, as thefirst, but the teaching-learning process takes place in college only. Third, the teaching-learning process is conducted in college and without collaboration. Students are divided  into small groups of 3 or 4 to make marketable products.  The products  are measured by some college aspects according to industrial standards, whereas co-operative attitudes are measured by Johnson and Johnson definition. The results are subjected to nonparametric statistic analyses. In perspective of the practice product, the first teaching-learning model does not differ significantly from the teaching learning second model (t = 2,2; P 0.05); but differs  significantly from the third  (t  = 4.5;  pO.Ol);  the  second   teaching-learning   model  differs significantly from  the third (t  = 3.7; pO.Ol). In perspective  of the co operative  attitudes,   the first   teaching-learning   model  does  not  differ significantly from  the second (t=0.81; p0.05).  The guest lecturer model is able toproduce marketable products and well co-operative attitudes in a team work.Keywords: collaborative   teaching-learning   model,   well   industry,  dual education system, guest lecturing, practice products, co-operative attitudes, teamwork